2011
DOI: 10.2215/cjn.01990211
|View full text |Cite
|
Sign up to set email alerts
|

Urine Volume and Change in Estimated GFR in a Community-Based Cohort Study

Abstract: SummaryBackground and objectives The effect of increased fluid intake on kidney function is unclear. This study evaluates the relationship between urine volume and renal decline over 6 years in a large community-based cohort.Design, setting, participants, & measurements This prospective cohort study was undertaken in Canada from 2002 to 2008. We obtained 24-hour urine samples from adult participants with an estimated GFR (eGFR) Ն60ml/min per 1.73 m 2 at study entry. Percentage annual change in eGFR from baseli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
149
2
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(161 citation statements)
references
References 39 publications
(42 reference statements)
8
149
2
2
Order By: Relevance
“…Changes in eGFR per year during the study period were estimated using within-patient linear regression. A rapid decline in eGFR was defined as a decrease in eGFR (negative slope) of $5% per year (12) over the period baseline to 2 years.…”
Section: Methodsmentioning
confidence: 99%
“…Changes in eGFR per year during the study period were estimated using within-patient linear regression. A rapid decline in eGFR was defined as a decrease in eGFR (negative slope) of $5% per year (12) over the period baseline to 2 years.…”
Section: Methodsmentioning
confidence: 99%
“…The water intake should be suffi cient to compensate daily losses (4). An appropriate hydration can reduce the risk of several diseases and physiological disturbances as headaches, obstipation, urolithiasis and renal malfunction (5). However, water consumption habits are complex and receive under-attention when evaluating eating habits (6).…”
Section: Introductionmentioning
confidence: 99%
“…New studies are needed focusing on dietary intake and hydration status (5,6) and the present study aims to contribute to fi ll this research gap in children soccer players.…”
Section: Introductionmentioning
confidence: 99%
“…Water ingestion, which readily decreases circulating AVP/copeptin levels, may modify CKD progression. 52 Studies in the 5/6 nephrectomized rat model suggested that increased water intake decreases circulating AVP levels and slows down the progression of kidney disease. 53 Taken together, these data suggest that high levels of AVP may be deleterious for kidney function, either by a direct hemodynamic effect through V1a vascular receptors or through V2 tubular receptors.…”
Section: Discussionmentioning
confidence: 99%